2021
DOI: 10.1002/app.51673
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of cellulose nanofibers on the morphological behavior and dynamic mechanical thermal properties of extruded polylactic acid/cellulose nanofibril nanocomposite foam

Abstract: Polylactic acid (PLA) foams were introduced as a good substitute for oil-based foams. Much research has been done on the autoclave of PLA foam, but discontinuous processes are not attractive for industries. In order to reduce the distance between the PLA foaming process and industrialization, it is necessary to introduce continuous processes. In this work, two solutions to improve the foaming of PLA are presented: using the extrusion process and adding cellulose nanofibers. So, in this study, a twin screw extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…Sadeghi et al [ 73 ] added hydrophilic cellulose nanofibers (CNF) to PLA and prepared microporous foams by twin-screw extrusion foaming and found that the addition of CNF promoted cell nucleation and increased cell density. The molecular weight of pure PLA was reduced by about 25% after extrusion, probably due to the hydrolysis of ester groups that occurred during the melting process.…”
Section: Supercritical Co 2 Foaming Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Sadeghi et al [ 73 ] added hydrophilic cellulose nanofibers (CNF) to PLA and prepared microporous foams by twin-screw extrusion foaming and found that the addition of CNF promoted cell nucleation and increased cell density. The molecular weight of pure PLA was reduced by about 25% after extrusion, probably due to the hydrolysis of ester groups that occurred during the melting process.…”
Section: Supercritical Co 2 Foaming Technologiesmentioning
confidence: 99%
“…Sadeghi et al [ 73 ] reported preparing PLA/CNF composite foam materials by adding an appropriate amount of cellulose nanofibers (CNF) to PLA. The continuous extrusion foaming method was used to avoid the shortcomings of the discontinuous production of intermittent foaming and to meet the requirements of industrialization.…”
Section: Effect Of Modifications On Foaming Of Pla Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The major drawbacks of CNF are its poor thermal stability, flammability, and lack of functionality, which make it difficult to improve the thermal properties and impart functionalities in CNF composites 7,8 . Surface modification of CNF or combination with other inorganic nanomaterials for construction of composites can potentially make up these problems, but these approaches are usually complex, and could compromise the biocompatibility or biodegradable of CNF 9–12 . Therefore, it is still a challenging task to fabricate multifunctional CNF composites with good properties while maintain the intrinsic advantages of CNF.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Surface modification of CNF or combination with other inorganic nanomaterials for construction of composites can potentially make up these problems, but these approaches are usually complex, and could compromise the biocompatibility or biodegradable of CNF. [9][10][11][12] Therefore, it is still a challenging task to fabricate multifunctional CNF composites with good properties while maintain the intrinsic advantages of CNF.…”
mentioning
confidence: 99%